Essays on dsge models applied for a regional economy - Marchionatti, Carlos (2024)
The present work aims to study macroeconomic models applied to regional economies that use the DSGE methodology, as well as using a DSGE model to study the State of Rio Grande do Sul (RS), in Brazil, and also simulating its potential economic trajectory during the Fiscal Recovery Regime (FRR). The first essay addresses different works around the world using this methodology for regional (subnational) economies, demonstrating the relevance of the topic. In the second essay, a model first developed for a region of Japan, called Kansai, is applied to Rio Grande do Sul, being adapted to the State both in its parameterization and in its equation modeling (emphasis on the fiscal part of the government - division of government spending into local and central and inclusion of public investment). The model was named Kansai-RS, inspired by the SAMBA model, which is well-established in Brazilian macroeconomic/DSGE literature. Despite its limitations, the model presented interesting results and provided a starting point for the use of such methodology in Rio Grande do Sul. The dynamics of productivity in the economy of Rio Grande do Sul proved to be fundamental for the state?s development, as well as for the adequate utilization of public resources by the local government. In the third test, simulations using Kansai-RS were carried out regarding the Fiscal Recovery Regime, signed in 2021 by RS. The simulations showed that the debt index is not the most relevant factor; rather, it is the sustained growth of the state?s GDP. Without an increase in State productivity, the debt becomes recessive for RS. Lastly, we highlight that the present work contributes providing methodological review and empirical results